2014
DOI: 10.1007/s12263-014-0438-y
|View full text |Cite
|
Sign up to set email alerts
|

The intake of a high-fat diet and grape seed procyanidins induces gene expression changes in peripheral blood mononuclear cells of hamsters: capturing alterations in lipid and cholesterol metabolisms

Abstract: We previously demonstrated that hamsters that were fed either a standard diet (STD) or a high-fat diet (HFD) and treated with a grape seed procyanidin extract (GSPE) showed decreased adiposity and circulating levels of free fatty acids compared with hamsters treated with a vehicle (Caimari et al. in Int J Obes 37:576-83, 2013, doi:10.1038/ijo.2012). Here, we tested whether the gene expression changes in peripheral blood mononuclear cells (PBMCs) can reflect these metabolic effects and the dyslipidaemia produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…In contrast, the metabolic profile of PBMC evaluated at the molecular and biochemical levels was particularly close to the one observed in the AT. This is in line with similar conclusions draws in several studies in humans [ 45 ] and laboratory animals [ 16 , 44 ], specially concerning lipid metabolism [ 46 ]. In contrast to this, other metabolic features, like pentose phosphate potential seems to have a PBMC-specific behaviour, with a strong dependence on glucose uptake and phosphorylation and a lower induction capacity when compared to the AT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the metabolic profile of PBMC evaluated at the molecular and biochemical levels was particularly close to the one observed in the AT. This is in line with similar conclusions draws in several studies in humans [ 45 ] and laboratory animals [ 16 , 44 ], specially concerning lipid metabolism [ 46 ]. In contrast to this, other metabolic features, like pentose phosphate potential seems to have a PBMC-specific behaviour, with a strong dependence on glucose uptake and phosphorylation and a lower induction capacity when compared to the AT.…”
Section: Discussionsupporting
confidence: 92%
“…When compared to the results discussed above, the metabolic response observed in the PBMCs in the obese minipig at the fasting state seems to be coherent with the adaptations reported in the major organs involved in the intermediary metabolism. As in a previous study in hamsters [ 44 ] our results show that PBMC metabolism does not reflect that of the liver. In contrast, the metabolic profile of PBMC evaluated at the molecular and biochemical levels was particularly close to the one observed in the AT.…”
Section: Discussionsupporting
confidence: 75%
“…In particular, the in vivo hypotriglyceridemic effect of dietary procyanidins involves the activation of the farnesoid X receptor, the subsequent upregulation of the nuclear receptor small heterodimer partner expression and the downregulation of SREBP1 expression ( Del Bas et al, 2009 ). Another study also reports that the reduction of the lipid content in white adipose tissue and the improvement of plasma lipid profile induced by grape seed procyanidin traitement involve the activation of both β-oxidation and the glycerolipid/free fatty acid cycle ( Caimari et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flavanols (cathechins and procyanidins) have antioxidant/free radical scavenging abilities ( Galleano et al, 2010 ) and anti-inflammatory effects ( Terra et al, 2011 ). They correct lipid abnormalities associated with obesity ( Quesada et al, 2009 ; Caimari et al, 2013 ), prevent insulin resistance ( Al-Awwadi et al, 2005 ; Montagut et al, 2010 ) and exert protective effects against cardiovascular diseases ( Rasmussen et al, 2005 ; Corder et al, 2006 ). Anthocyanins limit weight gain, and improve lipid profiles, hepatic function ( Wu et al, 2013 ) and insulin resistance ( Nizamutdinova et al, 2009 ) associated with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…22 In particular, the study of Castell-Auvi et al 23 found that grape seed procyanidins had a lipid-lowering effect by improving beta-cell functionality. And Caimari et al 24 found the up-regulation of lipid-related genes involved in both the anabolic and catabolic pathways in response to procyanidin treatment. In addition, Rong et al 25 also reported that the litchi pericarp procyanidins could relieve the lipid disorder in Apo E-mice by regulating gene expressions involved in hepatic lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%